2019
DOI: 10.1111/cea.13308
|View full text |Cite
|
Sign up to set email alerts
|

Traffic‐related air pollution induces non‐allergic eosinophilic airway inflammation and cough hypersensitivity in guinea‐pigs

Abstract: Background:The pathogenesis and pathophysiology of eosinophilia-related chronic cough such as non-asthmatic eosinophilic bronchitis and cough variant asthma are still not clear.Objective: This study is to examine the potential role of traffic-related air pollution (TRAP) in eosinophilic inflammation and cough responses.Methods: Non-sensitized guinea-pigs were exposed to TRAP in an urban traffic tunnel or kept in a filtered air environment for 7 or 14 days. Reflexive cough was measured using citric acid and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
(56 reference statements)
2
18
0
Order By: Relevance
“…We also observed a mild increase in the percentage of eosinophils in BALF after citric acid inhalation, but not after cold exposure. The airway eosinophilia was comparable to that observed in our previous study (Xu et al, 2018) and was possibly related to epithelial injury in the airway induced by the cough itself and bronchoconstriction during the repeated inhalation of citric acid (Fang et al, 2019). Such phenomena can be more representative of, or applicable to, the disease process of chronic cough in humans.…”
Section: Discussionsupporting
confidence: 85%
“…We also observed a mild increase in the percentage of eosinophils in BALF after citric acid inhalation, but not after cold exposure. The airway eosinophilia was comparable to that observed in our previous study (Xu et al, 2018) and was possibly related to epithelial injury in the airway induced by the cough itself and bronchoconstriction during the repeated inhalation of citric acid (Fang et al, 2019). Such phenomena can be more representative of, or applicable to, the disease process of chronic cough in humans.…”
Section: Discussionsupporting
confidence: 85%
“…Previous evidence indicated that PM2.5 exacerbated accumulation of eosinophils and neutrophils into the airway submucosa [26,27]. Another study reached the same conclusion that PM2.5 caused signi cant increase of eosinophils and neutrophils in BALF over time [28]. Therefore, we believed the PM2.5-induced in ammatory injury was the combined action of type 1 and type 2 in ammation.…”
Section: Discussionsupporting
confidence: 54%
“…Rising levels of air pollution from industrial and traffic emissions have become a major threat to public health in China 28. It has been reported that pollutants can not only enhance cough reflex sensitivity, but also induce non-allergic eosinophilic airway inflammation 2930. In China, males account for over 80% of industrial workers31 and traffic police,32 as well as 95% of professional taxi33 and bus drivers,34 whose mean age was 37.6-38.5 years.…”
Section: Discussionmentioning
confidence: 99%